Ortega y Ayala face to the thematic of the novel (or face to face) - Viñas Piquer, David (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
In some of  his articles, Francisco Ayala discusses Ortega y Gasset's well-known diagnosis of the problem of the novel: that there is a lack of new topics. Ortega primarily based his views on the criteria of novelty and originality. Conversely, Ayala puts forward the theory that the lack of new topics is not symptomatic of the deterioration of the novel, but in fact demonstrates that the novel is always linked to some aspect of the human condition. This, he suggests, is why all novels treat the same topic. Human behaviour does not change; it obeys the same old impulses, thereby giving rise to repetitive situations. To Ayala's way of thinking, trying to avoid such repetition is a mistake. For him, the originality of a novel lies not in the subjects it treats, but rather in the writer's ability to communicate his of her view of the world through his or her own personal experience and sensibiliities.
Keywords: José Ortega y Gasset; Francisco Ayala; theory of novel